2011
DOI: 10.1021/bi2002967
|View full text |Cite
|
Sign up to set email alerts
|

Indolequinone Inhibitors of NRH:Quinone Oxidoreductase 2. Characterization of the Mechanism of Inhibition in both Cell-Free and Cellular Systems

Abstract: We describe a series of indolequinones as efficient mechanism-based inhibitors of NRH:quinone oxidoreductase 2 (NQO2) for use either in cellular or cell-free systems. Compounds were designed to be reduced in the active site of the enzyme leading to loss of a substituted phenol leaving group and generation of a reactive iminium electrophile. Inhibition of NQO2 activity was assessed in both cell-free systems and in the human leukemia K562 cell line. Inhibition of recombinant human NQO2 by the indolequinones was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…The ability of indolequinones to induce growth inhibition in human cancer cell lines was measured using the MTT assay as previously described. 16,17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of indolequinones to induce growth inhibition in human cancer cell lines was measured using the MTT assay as previously described. 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…58 In continuation of our studies on the synthesis and biology of indolequinones, we investigated a number of relatively simple tri- and tetra-substituted derivatives initially evaluating their cytotoxicity and also their metabolism by quinone reductase enzymes. 916 …”
Section: Introductionmentioning
confidence: 99%
“…By the same mechanism, related small molecules inhibit other enzymes with noncovalent FAD cofactors (e.g. NQO2 35 and KDM1A 36 ). Reaction of 3 by an analogous mechanism (Fig.3a, upper) would not, in our experiments, lead to enrichment of an enzyme bearing a noncovalently bound flavin, because covalency with the protein is required for retention on the resin and detection by SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…NQO2 stabilizes C/EBPα degradation mediated by 20S proteasomes [35]. We previously showed that NQO2 is a high affinity target protein of resveratrol: NQO2 binds resveratrol with K D ≤ 50 nM [36]; X-ray crystal analysis shows that binding to resveratrol occurs in a hydrophobic pocket located between dimeric NQO2, possibly where the cosubstrate NRH binds [37]. Since the plasma concentration of resveratrol in humans can reach from 0.5 μM [38] to as high as 4 μM [39,40], it may be suggested that in vivo levels of resveratrol are sufficient for binding and inhibiting NQO2 enzyme activity and modulation of its other functions.…”
Section: Aversion Of C-myc Metabolic Addiction Using Resveratrol and mentioning
confidence: 99%